“Cite as U Write (CAUW)” an approach for efficient research writing and publication - N Shah, Jay; Shah, Sanjeeb; Shah, Jesifei; Malla, Ashesh (Journal of Chitwan Medical College, 2025)
Research writing is demanding, tiresome and time-consuming. Drafting, doing multiple revisions and saving new versions in different names makes it almost impossible to comprehend the revisions, often losing track of the original draft. Combining the literature search, incorporating citations, and accurately referencing them further adds to the problem. This editorial on "Cite as U Write (CAUW)” summarises how researchers can efficiently implement literature search, build library and execute in-text citation in Microsoft Word review mode with track change enabled, utilising Google Scholar or other search, and Zotero (or other reference management software); all at once in a single, well-tracked document in CAUW process. The process helps in reducing errors, saving time, and ensuring academic integrity by avoiding plagiarism. The CAUW is a cyclic workflow for an efficient writing approach, highly recommended for research writing and publication.